Aid and investment in statistics for Africa - Jeffery I. Round (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
Over many past decades countries in sub-Saharan Africa have received extensive bilateral and multilateral aid in support of the production of relevant, timely, and good quality data and statistics. But assessing aid effectiveness in the statistical area is a complex matter. Many datasets are effectively (global) public goods, as any restrictions on their availability and use are eventually relaxed. Hence it is extremely difficult to value or even measure the eventual impact of data production on general well-being. The aim of this paper is to review and scope how aid effectiveness might be assessed in this area. It sets out the context, the issues, and some possible approaches, going beyond existing measures of statistical capacity-building.
Keywords: C80; C81; C82; O55; 330; aid; statistics; Africa